Yokukansan, a Traditional Japanese Medicine, Enhances the Glutamate Transporter GLT-1 Function in Cultured Rat Cortical Astrocytes. (6th May 2018) - Ueki, Toshiyuki; Kawakami, Zenji; Kanno, Hitomi; Omiya, Yuji; Mizoguchi, Kazushige; Yamamoto, Masahiro
Abstract : Astrocytes carry two glutamate transporters—GLAST and GLT-1—the latter of which is responsible for >90% of glutamate uptake activity in the brain; however, under culture conditions, the GLT-1 expression in astrocytes is exceedingly low, as is the glutamate uptake activity mediated by GLT-1. This study aimed to elucidate the effects of yokukansan (YKS) in relation to the GLT-1-mediated regulation of extracellular glutamate concentrations. Thus, we treated cultured astrocytes with tumor necrosis factor- α (TNF- α ) and dibutyryl-cAMP (dBcAMP) (hereinafter, referred to as "TA") to increase GLT-1 expression and then functionally examined how YKS would affect glutamate uptake ability derived from GLT-1. Contrary to expectations, although the TA treatments did not affect the uptake activity, YKS significantly augmented it. Conversely, GLAST-derived glutamate uptake was significantly reduced by TA treatments but was unaffected by YKS. Subsequently, we analyzed the GLT-1 protein and mRNA levels and found that TA treatments had significantly increased them, which were then further augmented by YKS. These findings suggest that YKS enhances GLT-1-derived glutamate transport functions in TA-treated cultured astrocytes and that this process entails increased GLT-1 protein and mRNA levels. This type of mechanism may contribute to the YKS-mediated regulation of extracellular glutamate concentrations.